Stimulus cueing in blindsight. - Cowey, A; Stoerig, P (2004)
When visual stimuli are presented in the cortically blind visual field of patients or monkeys with verified destruction of striate cortex, many subjects can voluntarily respond to them. In studies of this blindsight, the on- and/or offset of the visual stimulus is usually known to the subject, either because it is signaled in some way or because the subject can present the stimulus himself. To study the effect of stimulus uncertainty on the responses of four hemianopic monkeys and one human hemianope, we compared trials on which the subjects themselves could instantly trigger the stimulus with trials on which the same stimulus appeared 1-7 s after the start-light that normally served as the trigger was first touched. The latter manipulation diminished both the percentage of trials on which the subjects responded and the percentage correct when they did respond. As the start-light disappeared when touched in the first but not second condition, we interpret our results as indicating an influential role for attention in blindsight. Although keeping attention focused on the start-light and delaying the target impaired performance especially in the monkeys, localization was still significant in three and hardly affected in GY.